The consequences of severe acute respiratory syndrome coronavirus-2 on acute kidney injury among iraqi patients - Zahraa Faris Al-Khero; Zahra'a Abd Al-Aziz Yousif; Hamzah Abdulrahman Salman; Allaa Hatim Thanoon (Biomedical and Biotechnology Research Journal, 2023)
Background: COVID-19 is considered one of the most infectious diseases that can spread by air droplets and can cause serious complications in the respiratory tract, also could affect many organs like the kidney and causing acute kidney injury (AKI). The study aimed to evaluate the status of the kidney function of patients who are infected with COVID-19 and how the virus is involved in AKI. Methods: The research was conducted from 15 January to 25 February 2021. One hundred patients (56% of males and 44% of females) were involved in the present study. All the samples were tested for COVID-19 using real-time reverse transcription polymerase chain reaction. Kidney function tests such as serum creatinine and blood urea, as well as COVID-19 infection severity measurements such as level of ferritin, D-dimer, and C-reactive protein (CRP) were tested for all patients. Results: All enrolled patients were positive for COVID-19. All the patients (100%) were positive for AKI (the mean of urea and creatinine were 78.87 mg/dl, and 2.16 μg/ml, respectively) and the mean age was 66.9 years. The infection severity was high as the level of ferritin (729.19 ng/ml), D-dimer (3.84 μg/ml), and CRP (71.87 mg/L) were high compared to normal values. The study revealed that AKI is probably worsened by COVID-19 infection, which is also connected to the greater severity of the disease. Conclusion: According to the results, we found a direct link between COVID-19 infection and the development of AKI. The study recommended giving critical care and attention with respect to kidney function to those who had COVID-19 infection.